(untitled) (Annals of the University of Bucharest. Geography Series, 2025)
In the specialized literature, urban risk is defined in a very simple way, as the risk linked to the territory of the city. In this study, we study the risks that have arisen in the city of Maroua, capital of the Far North Region of Cameroon. The realization of this study mobilized both factual and geo-historical data. Simple descriptive statistical analyzes were then performed. According to the archives available from the various administrations, the oldest documented disaster in the city of Maroua dates back to 1991, mainly floods, epidemics of meningitis and cholera. We note that traffic accidents and fires, which generally take place in very specific neighborhoods and on very specific axes, come first with 831 and 604 cases respectively. In addition, the documentation of catastrophic events is still very poor, because it does not allow an assessment of their real impacts, and no social disaster such as generalized fights or interethnic conflicts has been reported in the city despite its cosmopolitan character.